Relation of some motoric abilities with readiness-to-school test with girls aged five - Jakimovski M.; Shukova Stojmanovska D.; Georgiev G. (Faculty of physical education, sport and health, 2018)
The purpose of this research is related to the relationship between motor skills and the test for school readiness in girls. The sample of respondents in this research is 70 girls aged 60 to 66 months (5 to 5.5 years) from two kindergartens from Stip. 15 motor tests were applied - three for assessment of: coordination, flexibility, balance, precision and explosive power. To assess girls' readiness for school, a special test consisting of 5 subtests for determining the pre-knowledge of girls was applied. The obtained results from the regression analysis show that a statistically significant prediction among the five most important motor tests (predictor system of variables) and school readiness tests is only determined in the numerical test for school readiness.
Keywords: preschool age, kindergarten, children's pre-knowledge, regression analysis